Parental Diet Exposure and High-Sugar-Fat Intake Effect on Glucose, Triglyceride and Cholesterol Hemolymph Level of Drosophila melanogaster across Five Generations - Pertiwi, Kartika Ratna; Kuswandi, Paramita Cahyaningrum; Anazifa, Rizqa Devi; Zain, Haniza Hanim Mohd (Biosaintifika: Journal of Biology & Biology Education, 2025)
Metabolic syndrome (MetS) is influenced by parental traits and diet. Drosophila melanogaster is a potential disease model organism, sharing physiology and genetic similarities with humans. Previous research had focused on Drosophila melanogaster as a model organism for obesity and diabetes, but not for MetS. This research aimed to determine the effect of both parental diet and high sugar fat (HSF) intake on glucose, cholesterol, and triglyceride hemolymph levels of Drosophila melanogaster. Wild flies were purified in either control (standard) or MetS media (extra 3% sucrose and palm oil). Seventy-five pairs were divided into 5 groups, according to parental origin and feeding media, and maintained in five generations (F1-F5). Glucose, triglyceride, and cholesterol levels were measured using a colorimetric assay in three replications of each generation per group. Glucose, triglyceride, and cholesterol levels were significantly different in all treatment than control groups, and across generations in each group (p<0.05). Higher glucose and triglyceride levels appeared in the youngest generation (F5) of all groups, and in the flies reared on HSF diets. Maternal HSF-exposed groups demonstrated a more pronounced impact of parental metabolic-state on the glucose and triglyceride levels of the earlier generation. These findings highlight that parental exposure to HSF and prolonged HSF intake independently and synergistically lead to persistent and amplified metabolic dysregulation across generations. Drosophila melanogaster, modeled in this study, represents a novel experimental organism that is suitable for studying the epigenetics of MetS, gaining more consideration for the metabolic health consequences of long-term dietary habits and parental metabolic-state.